ANALISIS KEPUASAN PENGGUNA APLIKASI PENILAIAN PRESTASI KERJA (SKP ONLINE) MENGGUNAKAN METODE HUMAN ORGANIZATION TECHNOLOGY (HOT) FIT PADA BADAN KEPEGAWAIAN DAERAH KOTA PADANG - Primadani Viandra; Titi Sriwahyuni; Muhammad Anwar (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2017)
This study is aimed to describe user satisfaction on application applied at BKD Kota Padang, based on system quality, information quality, service quality, service quality and structure of organization aspects. This research has also analysed the effect of Human Organization Technology method to users’ satisfaction of SKP Online system. Survey method was used by sampling to end user of SKP Online as the population. By purposive sampling technique, this research selected limited respondent of 55 users. Descriptive analysis, inferential analysis and multiple regression have utilized to analyse the data and making decision as research result. However, the study result have shown that system quality, information quality, service quality and structure of organization are simultaneously affecting the users’ satisfaction variable and giving contribution of 48,4%. It means that improving many factors as above will absolutely increase the quality and users’ satisfaction of online SKP system as well.  Keyword     : Human Organization Technology, SKP Online, User Satisfaction.